Increase in energy cost of running at the end of a triathlon - Guezennec, C. Y.; Vallier, J. M.; Bigard, A. X.; Durey, A. (European Journal of Applied Physiology, 1996)
The purpose of the present study was to verify the increase in energy cost of running at the end of a triathlon. A group 11 trained male subjects performed a triathlon (15-km swimming, 40-km cycling, 10-km running). At least 1 week later the subjects ran 10-km as a control at the same pace as the triathlon. Oxygen uptake (VO2), ventilation (VE) and heart rate (HR) were measured during both 10-km runs with a portable telemetry system. Blood samples were taken prior to the start of the triathlon and control run, after swimming, cycling, triathlon run and control run. Compared to the control values the results demonstrated that triathlon running elicited a significantly higher (P < 0.005) mean VO2 [51.2 (SEM 0.4) vs 47.8 (SEM 0.4) ml.min-1.kg-1] VE [86 (SEM 4.2) vs 74 (SEM 5.3) l.min-1], and HR [162 (SEM 2) vs 156 (SEM 1.9) beats.min-1)]. The triathlon run induced a greater loss in body mass than the control run [2 (SEM 0.2) vs 0.6 (SEM 0.2) kg], and a greater decrease in plasma volume [14.4% (SEM 1.5) vs 6.7% (SEM 0.9)]. The lactate concentrations observed at the end of both 10-km runs did not differ [2.9 (SEM 0.2) vs 2.5 (SEM 0.2) m.mol.l-1]. Plasma free fatty acids concentrations were higher (P < 0.01) after the triathlon than after the control run [1.53 (SEM 0.2) to 0.51 (SEM 0.07) mmol.l-1]. Plasma creatine kinase concentrations rose under both conditions from 58 (SEM 12) to 112 (SEM 14) UI.l-1 after the triathlon, and from 61 (SEM 7) to 80 (SEM 6) UI.l-1 after the control run. This outdoor study of running economy at the end of an Olympic distance triathlon demonstrated a decrease in running efficiency.